Uncivil city : ecology, equity and the commons in Delhi - Baviskar, Amita (Thousand Oaks ; New Delhi : SAGE Publications India Pvt Ltd, 2020)
"To examine this contradiction, Uncivil City: Ecology, Equity and the Commons in Delhi looks at two decades of environmental politics in Delhi-across homes and workplaces, ordinary streets and extraordinary spectacles, and the river and the Ridge. It argues that the terms of the discourse-what is an environmental issue, who is authorised to speak, and which modes of action count as legitimate-are partial, particularistic and perverse"--